Can soap be a sustainable alternative to petroleum-based thermal insulation?. Issue 2 (11th May 2015) - Read, Lee; Arayici, Yusuf
Abstract : Purpose: – Thermal insulation is important to achieve energy efficiency in a buildings' lifespan while maintaining comfort. Traditionally, the majority of insulation in buildings is man-made petroleum based products with limited or no-end life usage. However, from an environmental and economic sustainability perspective, they are not sustainable as natural resources are finite and in danger of run-out. Furthermore, they are also highly influenced by the increasing price and the ongoing scarcity of fossil fuel oils. The paper aims to discuss these issues. Design/methodology/approach: – This paper introduces soap based insulation from recycled materials as a sustainable alternative to petroleum counterparts. The methodology is lab based experimentation and iterative tests. The phased based research process for the incremental development of the soap based thermal insulation is explained. Findings: – Findings reveal that soap based insulation can be one possible way forward in the quest for natural and sustainable thermal insulation from recycled products to preserve and conserve the sustainable environment. Originality/value: – Thus, the paper provides a unique environmentally friendly approach as an alternative to those existing petroleum counterparts for thermal insulation in buildings.